THE MEANING OF CULTURAL SIGNS AND VALUES IN THE MANGGARAI TRADITIONAL MARRIAGE TRADITION, NORTH SATARMESE DISTRICT - Imun, Alfiana; Martono, Boedi; Sugianto, Iwan (Transpublika Publisher, 2023)
This study aims to determine the cultural process of Manggarai traditional marriage, North Satarmese District, as well as to find out the meaning of traditional signs and the traditional cultural values in Manggarai traditional marriages, North Satarmese District. This is a descriptive qualitative research. The data sources used in this study are primary sources because the community leaders and traditional leaders in Manggarai are very helpful in getting information about this research. Data collection techniques used in this study were interviews, observation, and documentation. Analysis of the data used in this study is the recorded data is transcribed from the form of recordings and writings, the transcribed data is then translated into Indonesian, separates the transcription of data in the form of the meaning of signs and values related to the Manggarai traditional marriage ceremony, North Satarmese sub-district, Identification and grouping of data which is in accordance with the direction of the research study, and concludes the results of the analysis based on the previous description. The results showed that in Manggarai traditional marriages there were marriage processions, namely Pongo (pre-marriage), Tuke Mbaru (promising ceremony), Tukar Kila (ring exchange) Bantang (pre-wedding), Kawing (married), Paca (belis), Podo (delivering the bride to the the groom's village). The meaning of signs in traditional Manggarai marriages are gerep ruha (stepping on eggs), pentang pitak (cleaning mud), tukar kila (rings exchange), and paca (belis). Cultural values contained in Manggarai traditional marriages are, economic values, religious values, social values, moral values, and religious values.